Intense fluorescence of Au20 - Yu, Chongqi; Harbich, Wolfgang; Sementa, Luca; Ghiringhelli, Luca M.; Aprá, Edoardo; Stener, Mauro; Fortunelli, Alessandro; Brune, Harald (Journal of Chemical Physics, 2017)
Ligand-protected Au clusters are non-bleaching fluorescence markers in bio- and medical applications. Here we show that their fluorescence can be an intrinsic property of the Au cluster itself. We find a very intense and sharp fluorescence peak located at λ=739.2 nm (1.68 eV) for Au20 clusters in a Ne matrix held at 6 K. The fluorescence reflects the Highest Occupied Molecular Orbital-Lowest Unoccupied Molecular Orbital (HOMO-LUMO) diabatic bandgap of the cluster. Au20 shows a very rich absorption fine structure reminiscent of well defined molecule-like quantum levels. These levels are resolved since Au20 has only one stable isomer (tetrahedral); therefore our sample is mono-disperse in cluster size and conformation. Density-functional theory (DFT) and time-dependent DFT calculations clarify the nature of optical absorption and predict both main absorption peaks and intrinsic fluorescence in fair agreement with experiment.
CRIS-Team Scopus Importer:2023-09-25